Implementasi Kebijakan Perda No. 2 Tahun 2013 (Rencana Tata Ruang Wilayah) dalam Rangka Mewujudkan Good Environmental Governance di Kabupaten Seluma, Provinsi Bengkulu ( Studi implementasi setelah 2 tahun perjalanan Perda ) - Mukminin, Miftakhul; Astuti, Puji; Widayati, Wiwik (Journal of Politic and Government Studies, 2014)
Local urban planning spatial sound in the environment is very important to realize the spacethat is safe, comfortable, productive and sustainable. Good spatial plan was drawn up with dueregard to environmental sustainability and the condition of the area must be considered so that theresulting space use plan can be efficiently and optimally. To achieve environmentally sounddevelopment that have aspired. Implementation success is influenced by three basic things thathave a big impact on the implementation, human resources, the attention of governments and theproblems that arise.As a newly established district after the Regional Autonomy Law enacted, precisely since 2003Seluma District needs to develop sustainable regional development through regional spatialplanning. The results of this study describes journey the implementation of Regulation No. 2 in 2013Seluma District for two year journey and its application areas. The data used in this study isqualitative data, ie data and tend to use a descriptive analysis of the study results. Thus this studywill describe the facts and explain the circumstances of the object of research based on interviewsthat exist.The results of this study describes the journey of implementing regulations No. 2 in 2013Seluma District since 2012 to 2014. The basic factors constrain implementation, such as humanresources government officials, economic factors, public ignorance of the rules, as well as lack ofsocialization goes well. District of spatial plans is very important Seluma known, adhered to andmonitored by the community to achieve the spatial be better based on the environment.